Knowledge of Displaced Women in Relation to Family Planning in Kirkuk City - Darya Yassin Mustafa (Kufa Journal for Nursing Sciences)
Background: Family planning method which is safe and effective for every woman makes her able to protect her and her children health. More than half of the couples in developing world are using family planning to delay space or limit future pregnancy.